Heterosis and combining ability study for yield and quality traits in castor (Ricinus communis L.): HETEROSIS AND COMBINING ABILITY IN CASTOR - M S PATEL; R M CHAUHAN (Journal of Oilseeds Research, 2013)
Heterosis and combining ability study for yield and quality traitsin castor [Ricinus communis(L.)]" was carried out through diallel analysis at Main Castor-Mustard Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar. The experimental material composed of 45 hybrids, 10 parents and standard check GCH 5.The analysis of variance showed highly significant differences among genotypes and hybridsfor all the traits. Parents also differed significantly for all the charactersindicating considerable amount of genetic variability present in the experimental material. The average performance of hybrids differed from that of the parents for days to flowering, daysto maturity,seed yield /plant, oil content in seed and oil content in endosperm. Exploitable heterosis for seed yield/plant was observed in crosses HC 8 x 37504 (155.2%), PRT 44 x 37504 (99.1%), 37504 x 37500 (86.8%) and SKI 1 x 37500 (79.5%), whereas, cross HC 8 x 37504 (149.8%) and PRT 44 x 37504 (86.2%) recorded high heterobeltiosis for seed yield/plant. Crosses showing heterosis for seed yield exhibited noticeable heterosis through important yield components like days to maturity, days to flowering, stem length, oil content in endosperm and oil content in seed. The analysis of variance for combining ability showed highly significant differences for all the traits under investigation. The predictability showed that non-additive gene action was primarily involved in the inheritance ofthe characters viz., daysto flowering, daysto maturity,seed yield/plant, oil content in seed, endosperm content and oil content in endosperm. Additive gene action was found predominant for stem length, number of effective branches/plant and 100 seed weight. The parent, 37504 was a good combiner for seed yield/plant, while SKI-1 proved good combiner for oil content in seed. The ranking of parents based on gca effects was almost similar to that based on per se performance for most of the characters. Two hybrids SKI-1 x 37500 and HC-8 x 37504 exhibited significant and positive sca effects for seed yield per/plant. The cross HC-8 x 37504 gave highest seed yield/plant which had poor x good general combining parents.